The association of smoking status with SARS‐CoV‐2 infection, hospitalization and mortality from COVID‐19: a living rapid evidence review with Bayesian meta‐analyses (version 7). (17th November 2020) - Simons, David; Shahab, Lion; Brown, Jamie; Perski, Olga
Abstract: Aims: To estimate the association of smoking status with rates of (i) infection, (ii) hospitalization, (iii) disease severity and (iv) mortality from SARS‐CoV‐2/COVID‐19 disease. Design: Living rapid review of observational and experimental studies with random‐effects hierarchical Bayesian meta‐analyses. Published articles and pre‐prints were identified via MEDLINE and medRxiv. Setting: Community or hospital, no restrictions on location. Participants: Adults who received a SARS‐CoV‐2 test or a COVID‐19 diagnosis. Measurements: Outcomes were SARS‐CoV‐2 infection, hospitalization, disease severity and mortality stratified by smoking status. Study quality was assessed (i.e. 'good', 'fair' and 'poor'). Findings: Version 7 (searches up to 25 August 2020) included 233 studies with 32 'good' and 'fair' quality studies included in meta‐analyses. Fifty‐seven studies (24.5%) reported current, former and never smoking status. Recorded smoking prevalence among people with COVID‐19 was generally lower than national prevalence. Current compared with never smokers were at reduced risk of SARS‐CoV‐2 infection [relative risk (RR) = 0.74, 95% credible interval (CrI) = 0.58–0.93, τ = 0.41]. Data for former smokers were inconclusive (RR = 1.05, 95% CrI = 0.95–1.17, τ = 0.17), but favoured there being no important association (21% probability of RR ≥ 1.1). Former compared with never smokers were at somewhat increased risk of hospitalization (RR = 1.20, CrI = 1.03–1.44, τ = 0.17), greater disease severity (RR = 1.52, CrI = 1.13–2.07, τ = 0.29) and mortality (RR = 1.39, 95% CrI = 1.09–1.87, τ = 0.27). Data for current smokers were inconclusive (RR = 1.06, CrI = 0.82–1.35, τ = 0.27; RR = 1.25, CrI = 0.85–1.93, τ = 0.34; RR = 1.22, 95% CrI = 0.78–1.94, τ = 0.49, respectively), but favoured there being no important associations with hospitalization and mortality (35% and 70% probability of RR ≥ 1.1, respectively) and a small but important association with disease severity (79% probability of RR ≥ 1.1). Conclusions: Compared with never smokers, current smokers appear to be at reduced risk of SARS‐CoV‐2 infection, while former smokers appear to be at increased risk of hospitalization, increased disease severity and mortality from COVID‐19. However, it is uncertain whether these associations are causal.